Work Readiness of Building Engineering Education Students with Initial Knowledge Predictors - Metsi Daud; Djubir R. E. Kembuan (Journal on Education, 2025)
This research aims to analyze: (1) the relationship between initial abilities and work readiness of building engineering education, faculty of engineering, Unima students. The research design is quantitative research with a correlational research approach, using simple regression analysis. From the research results: 1) there is a significant relationship between initial ability and work readiness, providing a contribution of 43.56%. Thus it can be concluded: that increasing initial knowledge includes the results of mastering knowledge based on the cognitive aspects of remembering (C1), understanding (C2), application (C3), and analysis (C4), which is expected to increase work readiness in the form of having logical and objective considerations. , have the ability and willingness to work together with other people, be able to control oneself and have a critical attitude, have the courage to accept individual responsibility, have the ambition to progress and try to keep up with developments in the field of expertise, mental readiness. Or in increasing work readiness you must pay attention to initial knowledge that actually makes a significant contribution. With conducive initial skills, it is hoped that students will be able to provide maximum work readiness. In other words, having high initial abilities can foster good or high student work readiness